Hukum Membuka Aib Pasangan Suami Istri dalam Konseling Keluarga Perspektif Maqashid Syariah Imam Al- Ghazali (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study discusses two conflicting laws in family counseling practice, namely the principle of openness in family counseling, which requires the client to fully disclose their problems, and Islamic teachings that forbid a wife or husband from revealing their partner's faults to others. The purpose of this study is to analyze Imam Al-Ghazali's perspective on maqashid al-shariah regarding the law of disclosing a partner's faults in family counseling. The method used is a qualitative approach, analyzing Imam Al-Ghazali's opinions and types of maqashid shariah related to family counseling practice. This is a literature review study with primary sources from books of fiqh, journals, and related documents. The findings conclude that disclosing a partner's faults in family counseling is allowed if it falls into the category of dharuriyat (urgent needs) to protect al-kulliyyat al-khams (religion, life, mind, offspring, and wealth). It should not merely serve the needs of hajiyat or tahsiniyat. Based on the principle of al-dharurat tubih al-mahzurat, this law falls under al-ibahah al-muqayyadah (restricted permissibility), requiring its implementation in the right forum, by competent parties, with confidentiality maintained and minimizing harm for the greater good.